Rotation in 3D - Harder Version

Geometry Level pending

Two points A ( 7 , 4 , 1 ) , B ( 5 , 1 , 5 ) A(7,4,1) , B(5,-1,5) undergo a rotation about an unknown axis and through an unknown angle such that their images are A ( 6 , 3 , 6 ) , B ( 10 , 8 , 8 ) A'(6,3,6), B'(10,8,8) . Find the image of point C ( 4 , 5 , 6 ) C(4,5,6) under the same rotation. If the image is C ( x , y , z ) C'(x,y,z) then enter the value of 9 ( x + y + z ) 9( x + y + z ) .


The answer is 158.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

First some calculations:
\

A A = ( 1 1 5 ) \overrightarrow{A{A}'}=\left( \begin{matrix} -1 \\ -1 \\ 5 \\ \end{matrix} \right) , B B = ( 5 9 3 ) \overrightarrow{B{B}'}=\left( \begin{matrix} 5 \\ 9 \\ 3 \\ \end{matrix} \right) . \

A C = ( 3 1 5 ) A C = ( 3 ) 2 + 1 2 + 5 2 = 35 \overrightarrow{AC}=\left( \begin{matrix} -3 \\ 1 \\ 5 \\ \end{matrix} \right)\Rightarrow \left| \overrightarrow{AC} \right|=\sqrt{{{\left( -3 \right)}^{2}}+{{1}^{2}}+{{5}^{2}}}=\sqrt{35}
\

B C = ( 1 6 1 ) B C = ( 1 ) 2 + 6 2 + 1 2 = 38 \overrightarrow{BC}=\left( \begin{matrix} -1 \\ 6 \\ 1 \\ \end{matrix} \right)\Rightarrow \left| \overrightarrow{BC} \right|=\sqrt{{{\left( -1 \right)}^{2}}+{{6}^{2}}+{{1}^{2}}}=\sqrt{38}

\

Now, A A \overrightarrow {A{A}'} and B B \overrightarrow {B{B}'} are both perpendicular to the axis of rotation, hence, a direction vector of the axis is

d : = A A × B B = i j k 1 1 5 5 9 3 = ( 48 28 4 ) d:= \overrightarrow{A{A}'}\times \overrightarrow{B{B}'}=\left| \begin{matrix} \mathbf{i} & \mathbf{j} & \mathbf{k} \\ -1 & -1 & 5 \\ 5 & 9 & 3 \\ \end{matrix} \right|=\left( \begin{matrix} -48 \\ 28 \\ -4 \\ \end{matrix} \right) \

Since rotation about an axis is an isometry , we get the following equations:

A C = A C A C 2 = A C 2 ( x 6 ) 2 + ( y 3 ) 2 + ( z 6 ) = 35 ( 1 ) \left| \overrightarrow{{A}'{C}'} \right|=\left| \overrightarrow{AC} \right|\Leftrightarrow {{\left| \overrightarrow{{A}'{C}'} \right|}^{2}}={{\left| \overrightarrow{AC} \right|}^{2}}\Leftrightarrow {{\left( x-6 \right)}^{2}}+{{\left( y-3 \right)}^{2}}+\left( z-6 \right)=35 \ \ \ \ \ (1) and

B C = B C B C 2 = B C 2 ( x 10 ) 2 + ( y 8 ) 2 + ( z 8 ) = 38 ( 2 ) \left| \overrightarrow{{B}'{C}'} \right|=\left| \overrightarrow{BC} \right|\Leftrightarrow {{\left| \overrightarrow{{B}'{C}'} \right|}^{2}}={{\left| \overrightarrow{BC} \right|}^{2}}\Leftrightarrow {{\left( x-10 \right)}^{2}}+{{\left( y-8 \right)}^{2}}+\left( z-8 \right)=38 \ \ \ \ \ (2) Furthermore, C C \overrightarrow {C{C}'} is also perpendicular to d \overrightarrow{d} , hence,

C C d = 0 48 ( x 4 ) + 28 ( y 5 ) 4 ( z 6 ) = 0 ( 3 ) \overrightarrow{C{C}'}\cdot \vec{d}=0\Leftrightarrow -48\left( x-4 \right)+28\left( y-5 \right)-4\left( z-6 \right)=0 \ \ \ \ \ (3) Equations ( 1 ) (1) , ( 2 ) (2) and ( 3 ) (3) give two solutions: ( x , y , z ) = ( 159 35 , 46 7 , 367 35 ) and ( x , y , z ) = ( 55 9 , 74 9 , 29 9 ) \left( x,y,z \right)=\left( \frac{159}{35},\frac{46}{7},\frac{367}{35} \right) \ \ \ \ \ \ \text{and} \ \ \ \ \ \ \left( x,y,z \right)=\left( \frac{55}{9},\frac{74}{9},\frac{29}{9} \right) The first solution is rejected, since it leads to a point C {C}' for which A C A C \left| \overrightarrow{{A}'{C}'} \right|\ne \left| \overrightarrow{AC} \right| , while the second one satisfies the condition A C = A C \left| \overrightarrow{{A}'{C}'} \right|= \left| \overrightarrow{AC} \right| . Hence, the image of C C is C ( 55 9 , 74 9 , 29 9 ) {C}'\left( \frac{55}{9},\frac{74}{9},\frac{29}{9} \right) .

For the answer, x = 55 9 x=\dfrac{55}{9} , y = 74 9 y=\dfrac{74}{9} , z = 29 9 z=\dfrac{29}{9} , thus, 9 ( x + y + z ) = 158 9\left( x+y+z \right)=\boxed{158} .

Hosam Hajjir
Jul 23, 2020

The axis has to lie in a plane whose normal is ( A A ) (A - A') and passing through 1 2 ( A + A ) \frac{1}{2}(A +A') , and also in a plane whose normal is ( B B ) (B - B') and passing through 1 2 ( B + B ) \frac{1}{2} (B + B') . Thus the axis line is the intersection of these two planes. The equations are,

x + y 5 z = ( 1 , 1 , 5 ) ( 6.5 , 3.5 , 3.5 ) = 7.5 x + y - 5 z = (1, 1, -5) \cdot (6.5, 3.5, 3.5) = -7.5

5 x 9 y 3 z = ( 5 , 9 , 3 ) ( 7.5 , 3.5 , 6.5 ) = 88.5 -5 x - 9 y - 3 z = (-5, -9, -3) \cdot (7.5, 3.5, 6.5) = -88.5

the solution of this system of equations is the line

( x , y , z ) = ( 39 , 31.5 , 0 ) + t ( 12 , 7 , 1 ) (x, y, z) = (-39, 31.5, 0) + t (12, -7, 1)

so this is our axis of rotation. We still don't know the angle of rotation. So we set up the rotation equation for point A

A = p 0 + R ( A p 0 ) A' = p_0 + R (A - p_0)

here p 0 p_0 is any point on the axis of rotation, and R R is the rotation matrix and is given by

R = a a T + ( I a a T ) cos θ + S a sin θ ( ) R = a a^T + (I - a a^T) \cos \theta + S_a \sin \theta \hspace{12pt}(*)

where θ \theta is the angle of rotation about the axis whose unit direction vector is a a .

S a S_a is the skew-symmetric matrix which when multiplied by a vector b b results in the cross product a × b a \times b

Note that all quantities in equation ( ) (*) are known except θ \theta .

Plugging in a = ( 12 , 7 , 1 ) 1 2 2 + ( 7 ) 2 + 1 2 a = \dfrac{(12, -7, 1)}{ \sqrt{ 12^2 + (-7)^2 + 1^2 } } and p 0 = ( 39 , 31.5 , 0 ) p_0 = (-39, 31.5, 0) , and the coordinates of point A A , we obtain

( 6 , 3 , 6 ) = v 0 + v 1 cos θ + v 2 sin θ (6, 3, 6) = v_0 + v_1 \cos \theta + v_2 \sin \theta

since v 1 v_1 and v 2 v_2 are perpendicular to each other, then

cos θ = ( ( 6 , 3 , 6 ) v 0 ) v 1 v 1 v 1 \cos \theta =\dfrac{ ( (6, 3, 6) - v_0 ) \cdot v_1 }{ v_1 \cdot v_1 }

sin θ = ( ( 6 , 3 , 6 ) v 0 ) v 2 v 2 v 2 \sin \theta = \dfrac{ ( (6, 3, 6) - v_0 ) \cdot v_2 }{ v_2 \cdot v_2 }

and from this we can calculate θ 2.210188 \theta \approx -2.210188

Now the rotation is fully specified.

Now the image of point C C is given by,

C = p 0 + R ( C p 0 ) C' = p_0 + R ( C - p_0)

performing the calculations, we get C = ( 6 1 9 , 8 2 9 , 3 2 9 ) C' = ( 6 \frac{1}{9} , 8 \frac{2}{9} , 3 \frac{2}{9} )

so that 9 ( x + y + z ) = 158 9(x + y + z) = \boxed{158} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...